A flexible 1, 2-cis α-glycosylation strategy based on in situ adduct transformation. Issue 25 (15th June 2017) - Hu, Jhe-Cyuan; Feng, Ai-Fen Wendy; Chang, Bo-Yao; Lin, Chun-Hung; Mong, Kwok-Kong Tony
Abstract : Towards a universal 1, 2- cis α-glycosylation strategy using the joined forces of formamide and iodide nucleophile additives. Abstract : A flexible 1, 2- cis α-selective glycosylation strategy for a wide range of glycosyl donors and acceptors has been developed, which is based on an in situ adduct transformation protocol. Based on this strategy, both NFM-derived and iodide covalent adducts can be accessed for glycosylation. Using low temperature NMR spectroscopy, the aforementioned glycosyl adducts were detected.